The The Association of Single Nucleotide Polymorphism rs5883 in The CETP Gene with Oxidized-LDL Level in Coronary Atherosclerosis Patients: CETP gene and Coronary Atherosclerosis - K. Habash, Noor; Omar F. Abdul-Rasheed; Mustafa A. Salman (Iraqi Journal of Cancer and Medical Genetics, 2023)
Atherosclerosis is a progressive inflammatory disorder of the arterial wall and can affect any artery in the body. When it occurs in the heart (Coronary atherosclerosis), it can cause MI, angina, and even sudden death; in the brain, stroke, and transient ischemic attack; and in the limbs causing claudication and critical limb ischemia. CETP plays a role in transferring the cholesterol from peripheral tissues to the liver through the collection of triglycerides of VLDL and LDL for exchange by the cholesteryl ester of HDL. Therefore, it has a role in HDL metabolism by converting it to LDL and increasing the risk of incident atherosclerosis. Aim of the study: To investigate the rs5883 genotypes and their association with the coronary atherosclerosis and to study the impact of this SNP on the CETP gene with the lipid profile including the OX-LDL in patients and controls. Patients and method: All patients underwent angiography to confirm diagnosis in a case- control study, comparing 60 volunteers as the control group. The lipid profile test was measured by colorimetric method, Ox-LDL was measured by ELISA technique and the CETP SNP genotypes by RT-PCR technique. Results: There was a significant difference in genotypes in the rs5883 SNP, the heterozygous genotype (TC) was much more frequent in patients (20%) than controls (3.7%) with a significant difference (OR= 6.5, 95%CI=1.38-30.55). There was no association of this SNP with lipid profile, there was a significant impact of rs5883 with Ox-LDL, the medians of CT carriers significantly higher than CC genotypes.